Atlas of Genetic Diagnosis and Counseling - Chen, Harold (Humana Press : Imprint: Humana, 2006)
Many birth defects, although rare individually, are encountered in clinical practice and have now become treatable if properly diagnosed. In the Atlas of Genetic Diagnosis and Counseling, Harold Chen, MD, shares his almost 40 years of clinical genetics practice in a comprehensive pictorial atlas of 203 genetic disorders, malformations, and malformation syndromes. The author provides a detailed outline for each disorder, describing its genetics, basic defects, clinical features, diagnostic tests, and counseling issues, including recurrence risk, prenatal diagnosis, and management. Numerous color photographs of prenatal ultrasounds, imagings, cytogenetics, and postmortem findings illustrate the clinical features of patients at different ages, patients with varying degrees of severity, and the optimal diagnostic strategies. The disorders cited are supplemented by case histories and diagnostic confirmation by cytogenetics, biochemical, and molecular techniques, when available. Also available in a CD-ROM edition (ISBN: 1-58829-974-5). Authoritative and up-to-date, the Atlas of Genetic Diagnosis and Counseling will help all physicians to understand and recognize genetic diseases and malformation syndromes, and consequently better evaluate, counsel, and manage affected patients.